(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the effect of 400-meter interval training on improving VO₂Max endurance in Pencak Silat athletes in South Sulawesi. VO₂Max is a key indicator of aerobic capacity and plays a crucial role in sustaining high-intensity movements required in Pencak Silat performance. A total of 20 athletes participated in this study, using a pretest–posttest experimental design. VO₂Max measurements were conducted using the Beep Test to evaluate changes before and after the training intervention. The descriptive analysis showed an increase in the athletes’ VO₂Max from a pretest mean of 40.53 to a posttest mean of 45.21. The Shapiro–Wilk normality test indicated that both pretest and posttest data were normally distributed (p > 0.05). Furthermore, the paired sample t-test revealed a significant improvement in VO₂Max following the 400-meter interval training program (t = 94.50, p < 0.001). These results demonstrate that the interval training model effectively enhances the athletes’ aerobic capacity. In conclusion, the 400-meter interval training program has a significant positive impact on improving VO₂Max endurance in Pencak Silat athletes in South Sulawesi. The findings suggest that this training method can be recommended as an effective component of conditioning programs to enhance athlete performance in high-intensity combat sports.